Which Dimensions of Culture Matter for Long-Run Growth? - Gorodnichenko, Yuriy; Roland, Gerard (American Economic Review, 2011)
We present empirical evidence that, among a variety of cultural dimensions, the individualism-collectivism dimension, based on Hofstede's (2001) data, is the most important and robustly significant effect of culture on long run growth. Other dimensions that have a significant effect, albeit less robust, are generally strongly correlated with individualism and convey similar information. We found no significant or robust effect on growth from cultural dimensions that are independent from the individualism-collectivism cleavage.